Comparative Study Between Oil Analysis and Sludge Analysis of Marine Diesel Engines - NEJJAR, K.; ZERIOUH, A.; BELKBIR, L.; HAMAD, M. (Asian Journal of Chemistry, 2010)
This paper presents a comparative study between detecting metallic particales in the lubricating oil and the sludge by spectrometric analysis. The diesel engine is the key power equipment in ships so it is important to monitor wear state of the engine. The presence of increased levels of metallic particles in the engine reduces the lubricant effectiveness. Oil analysis is a useful method for forecasting wear trend and has been used in diesel engines successfully while the sludge analysis can provide several informations concerning the lubricant and the engine wear.